(untitled) (Amsterdam, 2007)
New Ecology presents an ecosystem theory based on the following ecosystem properties: physical openness, ontic openness, directionality, connectivity, a complex dynamic for growth and development, and a complex dynamic response to disturbances. Each of these properties is developed in detail to show that these basic and characteristic properties can be applied to explain a wide spectrum of ecological obsevations and convections. It is also shown that the properties have application for environmental management and for assessment of ecosystem health
Keywords: Ecology,Sinh thái; Research,nghiên cứu